Prevalence of glucose intolerance in rheumatoid arthritis patients at a tertiary care centre in Haryana. (December 2017) - Rajput, Rajesh; Dangi, Anoop; Singh, Harpreet
Abstract: Aims: Recent studies have shown increasing prevalence of dysglycemia in rheumatoid arthritis (RA) patients. The present study was planned to study the prevalence of pre-diabetes and diabetes in RA patients from a tertiary care centre in Haryana, India. Methods: 150 diagnosed cases of rheumatoid arthritis which were on follow up in Rheumatology clinic from last one year and equal number of age, sex matched controls were recruited for the study. FPG, 2 h plasma glucose level after 75 g oral glucose tolerance test and HbA1c were estimated in all the subjects. In RA patients c-reactive protein (CRP), erythrocyte sedimentation rate (ESR), rheumatoid factor (RF) and Anti-cyclic citrullinated (Anti CCP) antibodies were also measured and disease activity was assessed by using (DAS28 joint counts) and CDAI. Results: Patients with RA had statistically significant higher waist circumference, hip circumference and BMI as compared to control group. Prevalence of glucose intolerance in RA patients and control group was 14.67% and 6.67% respectively which was statistically significant (p = 0.025). The prevalence of pre-diabetes was in RA group was not significant statistically. There was higher disease activity in glucose intolerant (GI) RA cases as compared to normal glucose tolerant (NGT) RA cases. The most commonly used drug combination among RA patients was MTX + HCQ + SAAZ (49 patients, 32.67%). Maximum glucose intolerance was observed in patients who were on Non-HCQ drug combinations. Conclusions: There is elevated prevalence of glucose intolerance among RA patients that is related to high disease activity, visceral adiposity and drugs usage.